(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article examines the reforms being implemented in our country to prevent and combat corruption, the distinctive features of anti-corruption policy, the study of foreign systems in this field and the introduction of their positive aspects into practice. It also highlights the necessary measures to address existing problems and shortcomings, as well as theoretical and practical conclusions on improving the current legislation.